Making universal digital access universal: Lessons from COVID-19 in Singapore - NG, Irene Y. H. (Institutional Knowledge at Singapore Management University, 2022)
Digital resources—which include devices, internet connection and digital literacy—have become basic needs. Thus with the global COVID-19 pandemic having accelerated digitalization, the urgency for universal digital inclusion has hastened. Otherwise, digital inequality will lead to social inequality and impede social mobility. Using Singapore as a case study, this article applies the insights learned from a participatory action research to recommend a policy framework for universal digital access, with practical humanistic steps towards full digital inclusion. Singapore is a digitally advanced nation with almost universal digital availability, yet when COVID-19 forced rapid digital adoption, gaps in access by vulnerable groups such as low-income households, elderly and migrant workers were found. From the learning points on gaps and measures taken by community groups, volunteers and policy-makers in our research, we recommend making access to all three digital resources automatic and afordable, with an undergirding principle to implement technology among the most digitally excluded frst before national roll out. A public-community-corporate funding and partnership model is also proposed to sustain universal provision.